Local wisdom of Bonai people in Ulak Patian, Riau - Ryan Prayogi (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
This research aims to describe cultural values as local wisdom of the Bonai tribe in establishing the identity of a nation, particularly at Ulak Patian, Riau. This study uses a qualitative approach with ethnographic methods. Data collection techniques used are observation, interviews, documentation. The results of research on cultural values as the local wisdom of the Bonai tribe in Ulak Patian are carried out by declining ancestral heritage as traditional social attitudes and behavior. There are many types of local wisdom that are described in this article, which is a cultural identity possessed by the Bonai Tribe. This identity has been transformed as a cultural force that must be maintained until now. The current swift current of globalization makes all ethnic groups in Indonesia need to be kept their cultural identity.